Experience of prenatal consultation in Zaporizhzhia region over the 2011-2015 years - N. V. Avramenko; H. A. Lomeyko; O. A. Nikiforov; O. S. Sukhonos (Zaporozhye State Medical University, 2016)
Congenital malformations are one of the main causes of high infant mortality and disability from childhood. Medical and genetic counseling is an important integral part of prenatal diagnosis. Aim. The experience of the work of prenatal consultation at the clinic of Zaporizhzhya Regional Center of Human Reproduction for the 2011- 2015 years has been analyzed. Modern methods of prenatal diagnosis, including mass and selective testing of pregnant women on birth defects and chromosomal abnormalities by ultrasound examination and evaluation of maternal serum markers, as well as prenatal, cytogenetic diagnosis of chromosomal diseases in high-risk groups have been used for the early detection and prevention of birth of children with hereditary diseases in the Zaporizhzhia region. Methods and results. 2,528 Pregnant women with suspected congenital malformations of the fetus have been examined. To adequately assess the perinatal prognosis and develop tactics of pregnancy in the early neonatal period the diagnosis of pregnant women included consultation of geneticist, obstetrician - gynecologist, others specialists. Malformations of the fetus have been identified in 1.435 pregnant women. Conclusions. To identify chromosomal aberrations and congenital malformations in the fetus the prenatal consultation defines: the forecast for the life and health of the child, the tactics of pregnancy and birth, postnatal correction. Multiple malformations in the fetus and congenital central nervous system development occupy the first place in the structure of abortion during the observed period (2011-2015 years).